End of Life Care for People with an Intellectual Disability a Qualitative Exploration of Staff Carers' Experiences - Mc Carron, Mary; Burke, Eilish; Timmins, Fiona (My University, 2021)
Background: Although people with intellectual disability are increasingly living longer and experiencing high levels of multiple co-morbidity, palliative care has received limited attention among this population. There is some evidence that their needs are unattended and that more could be done to improve care services. Methods: 28 carers who cared for older people with intellectual disability at end of life were interviewed. Data were analysed using thematic analysis. Results: One major theme emerged relating to the practical management s of end of life care in formal institutionalised settings. Seven subthemes also emerged: pain, learned acceptance, transitions, decisions, conversations about dying, GP care, rapid decline and challenges with interventions. Conclusion: Gaps emerged in the care of the person with intellectual disability. Pain assessment and pain management are particular challenges. End of life care was not always effectively planned, and earlier intervention, including end of life conversations are needed. More needs to be done in terms of education for carers, health care workers, and especially those in the acute care setting and palliative care services who may be unfamiliar with the needs of this cohort.
PUBLISHED
Keywords: intellectual disability; older people; death; dying; end of life; palliative; care; Ageing; Ageing and intellectual disability; End-of-life; Intellectual Disability; OLDER PEOPLE; Palliative and end of life care; Palliative care; palliative care and intellectual disability; Age-related disability; Intellectual Disability